Evaluating Uncertainty Behaviors of Cognitive Users Against SSDF Attack for Cooperative Spectrum Sensing - Jingyu Feng; Jinlong Li; Guangyue Lu (Dianxin kexue)
Aiming at the uncertainty behaviors of cognitive users, an evaluation mechanism based on D-S theory, called HardGuard, was proposed to guard the hard-decision fusion schemes. Before fusing data, HardGuard will filter out false sensing data to avoid the impact of malicious users. The simulation results show that HardGuard is effective in suppressing spectrum sensing data falsification attack, and it can ensure the better sensing performance for the hard-decision schemes.